Evaluating Hepatitis B Immunity among Dentists in Babylon Provenance: A Cross-Sectional Study - Mohammed, Eman Hamza; Abed, Ahmed S. (Medical Science Journal for Advance Research, 2023)
Background: The cross-sectional study examines the immunization history, adherence to preventive measures, and demographic factors that interact with the hepatitis B immune status of a cohort of 85 dentists of Babylon heritage. The ages of the dentists vary from 22 to 46, and they have different immunization records and safety precautions. Hepatitis B immunity exhibits complex patterns that are revealed by a thorough examination of data, including gender, age, vaccination status, date of vaccination, number of doses, and adherence to preventive measures. Even if a certain number of dentists have foreseen and had immunizations, some differences among them in terms of compliance with the recommended preventive measures were observed. Different can indeed be stunning: unique vaccination schedules of the dentists create peculiar immunity rates. The hindrance of spread and developing of immunity may be facilitated by the adoption of preventive measures, which include personal protective equipment (PPE) use on regular basis. The study takes a different angle in the eyes of timeline by disclosing vaccination journeys that cover the two decades. The results stress upon the effectiveness of immunization campaigns and raise awareness on the crucial importance of continuing to implement precautionary measures in order to preserve immunity among our communities. This work may be helpful in designing targeted plans that take the individual peculiarities into account. Also, it contributes to the understanding of the hytic process of anti-hepatitis B in dentists. This evidence however is invaluable for the health care policies; it encourages regular testing and strengthens the preventative measures to achieve sustainable status for the health care workers on a long term basis. This article serves, undeniably, as a guidebook not only for the government workers and also the medical researchers engaged in the field of hepatitis B prevention programs. Taken together, the knowledge gathered applies to evidence-based interventions that ensure workers' protection against the hepatitis B spread, tackling the public health issues.